The Effect of Planting Media and Types of NPK Fertilizers (Compound and Mixed) on the Growth of Oil Palm Seedlings in Pre-Nursery - Firmansyah, Ivan Dwi; Rochmiyati, Sri Manu; Ardiani, Fani (ITScience (Information Technology and Science), 2024)
This study aims to determine the effect of planting media composition and types of NPK fertilizers (compound and mixed) on the growth of pre-nursery oil palm seedlings. The study was conducted in September - November 2023 at the Instiper Yogyakarta Education and Research Garden. This study used a factorial experimental method arranged in a completely randomized design (CRD) consisting of two factors, namely the composition of the planting media (clay, sand, sand + clay + organic fertilizer, sand + clay, clay + organic fertilizer, sand + organic fertilizer) and types of NPK compound fertilizers (compound fertilizer 15-15-15 and mixed fertilizer 0.30g Urea + 0.30g TSP + 0.25 g MOP). The results showed that the treatment of NPK fertilizer types (compound and mixed) and planting media composition interacted significantly with the height of pre-nursery oil palm seedlings, where the combination of clay soil media with mixed fertilizers produced a plant height of 25.90 cm. The treatment of planting media composition significantly affects the number of leaves, where the composition of sand + clay + organic fertilizer produces the highest number of leaves, which is 4 strands. Furthermore, treating NPK fertilizer types (compound and mixed) also significantly affects the diameter of pre-nursery oil palm seedlings, where using mixed fertilizers gives the highest stem diameter results, which is 9.46 cm.